The Degradation Results of Photovoltaic Modules under Outdoor Testing Conditions - Silsirivanich, Nitikorn; Palasai, Wasan (Princess of Naradhiwas University Journal, 2020)
This study presented the photovoltaic module (PV module) degradations of 1 mono-crystalline (c-si) panel, 1 poly crystalline panel and 2 thin-film solar panels (CdTe) under outdoor testing for 365 days. PV modules were tested by visual inspection test, insulation test, wet-leakage current test and standard electrical measurement under standard testing condition (STC) at the CES Solar Cell Testing Center (CSSC), King Mongkut's University of Technology Thonburi (Bang khun thian). All PV modules in this study were certified standard. Testing results showed that the degradation of the maximum power (Pmax) for both the mono-crystalline and the poly crystalline module were higher than the Thin-film modules. This study implied that the selling price of PV module could not guarantee the quality. The high-quality PV modules are subjected to approve by accredited laboratories under ISO17025 or the testing according to IEC 61215 and IEC 61646.